New synonymies and distribution records of some longhorn beetles (Coleoptera, Cerambycidae) occurring in South Africa - (:unkn) unknown (My University, 2023)
Zamium bicolor Distant, 1898 (currently Alocerus bicolor) is transferred to Pectoctenus and considered as the new senior subjective synonym of Pectoctenus bryanti Lepesme, 1948. Obrium rudebecki Tippmann, 1959 is transferred to the genus Duffyoemida and considered as the new senior subjective synonym of Duffyoemida barkeri Martins, 1977. The following additional new subjective synonym is proposed: Zamium prociduum Pascoe, 1864, is a junior synonym of Zamium bimaculatum (Fabricius, 1781). Stenobrium punctatum Adlbauer, 2007, Zambizus jeannae Juhel, 2016, Swaziphanes bimaculatus Adlbauer, 2002, Planodema bimaculata (Aurivillius, 1916), Stenidea (Amblesthidus) lateralis (Aurivillius, 1908) and Subinermexocentrus allardi Breuning, 1972, are recorded from South Africa for the first time. Host plants of Duffyoemida rudebecki (Tippmann, 1959), Swaziphanes bimaculatus and Zamium bimaculatum are reported for the first time.
Keywords: African Research